APPLICATION OF BALINESE ORNAMENT (KEKETUSAN KAKUL-KAKULAN) IN ENDEK WOVEN FABRIC WITH AIRBRUSH TECHNIQUE FOR EVENING DRESS - I Made Radiawan; Tjok Istri Ratna Cora Sudharsana; Ni Kadek Yuni Diantari (Yayasan Sinergi Widya Nusantara, 2022)
Purpose : The use of endek fabrics in creating evening clothing can increase creativity so that it can produce innovative evening dress designs with curvaceous ornaments, besides that it can be a cultural heritage. Research methods : The stages in the process of creating evening dress designs consist of three main stages, namely the idea stage, the mindmap method stage, and the design process stage. Findings : The creation of evening dress takes modern tradition as the concept. The traditional concept can be seen from the application of traditional Balinese ornaments, namely keketusan kakul-kakulan as a motif on endek woven fabrics with the airbrush technique. While the modern concept can be seen in the silhouette of the evening dress which is designed not out of date, unique and fashionable, and comfortable to use. Implications : Evening dress with endek woven fabric with a kakul-kakulan motif is one of the innovative evening wear choices for women to be used on formal occasions and as a form of appreciation for Balinese cultural heritage and endek cloth weavers